Fire behaviour of ecological soil-cement blocks with waste incorporation- experimental and numerical analysis - Ferreira, Débora (2019)
The increasing interest on earth construction as a sustainable building solution led to the development of modern earth construction techniques, in particular of masonry made of compressed earth blocks (CEBs). Soil is an abundant raw material, recyclable and reusable, noncombustible, non-toxic, with significant thermal behaviour and without too expensive transformation processes, which allows selecting this material as a major possibility for sustainable construction. The main goal of the present study is to assess the behaviour of soilcement blocks with incorporation of organic wastes. The problem of waste accumulation exists worldwide and has become a concern for today's society, leading to enormous environmental damage. One of the possibilities for reducing their environmental impact is the reuse of these wastes in new materials. However, incorporating wastes changes mechanical, physical and thermal properties of the new material. In order to evaluate the potential use of the wastes in blocks composition, laboratory tests were conducted and results were analysed [1]. This paper presents the fire behaviour of ecological soil-cement blocks with waste incorporation. At high temperatures, physical and mechanical changes were evaluated in the tested elements. Therefore, an experimental program was performed using samples of wall panel with soil-cement blocks. Previously, thermomechanical behaviour on cylindrical samples at different temperature ranges have been studied, [2]. The highest temperature tested was 600°C. The wall specimens under fire conditions were also analysed by a non-linear transient finite element numerical model, in time and temperature domains, and the numerical and experimental temperature fields compared.